2020
DOI: 10.1590/1678-4499.20200127
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with seaweed extract mitigate heat stress in spinach: effect on germination, seedling growth and antioxidant capacity

Abstract: Spinach seeds are sensitive to high temperatures during germination and plant growth.It is known that seed priming with water or with seaweed extract (SWE) may enhance germination and seedling growth. The objective of this study was to evaluate the effects of seed priming with SWE (Ascophyllum nodosum) on the germination, seedling growth and antioxidant capacity of spinach seedlings under conditions of heat stress. Five concentrations of SWE (0.0, 0.15, 0.30, 0.60 and 1.2%) were used for priming the seeds unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Seaweed extracts (SWE) derived by extracting several macroalgae species are now widely used substances having the potentiality to reduce adversity of abiotic stress, thus enhancing plant productivity [129]. Anjos Neto et al [130] experimented with five concen-trations of A. nodosum SWE in spinach seedlings under HT (30 • C) and observed that in both non-stressed and HT-stressed conditions, MDA and H 2 O 2 contents were reduced due to the application of 0.30% SWE. Furthermore, improved activity of antioxidant enzymes were also observed with SWE which could have reduced the oxidative degradation by lower MDA content and cell oxidative damage under HTs.…”
Section: High Temperaturementioning
confidence: 99%
“…Seaweed extracts (SWE) derived by extracting several macroalgae species are now widely used substances having the potentiality to reduce adversity of abiotic stress, thus enhancing plant productivity [129]. Anjos Neto et al [130] experimented with five concen-trations of A. nodosum SWE in spinach seedlings under HT (30 • C) and observed that in both non-stressed and HT-stressed conditions, MDA and H 2 O 2 contents were reduced due to the application of 0.30% SWE. Furthermore, improved activity of antioxidant enzymes were also observed with SWE which could have reduced the oxidative degradation by lower MDA content and cell oxidative damage under HTs.…”
Section: High Temperaturementioning
confidence: 99%
“…Various priming techniques are available to reduce the effects of stress factors which includes hydropriming, halopriming, osmopriming, hormonal priming and biopriming (Neto et al, 2020;Chakraborty and Dwivedi, 2021).…”
Section: Priming Methodsmentioning
confidence: 99%
“…Moreover, as shown in the latest study, the application of seaweed extract in combination with other biostimulants should be considered. Ascophyllum nodosum Soybean Expressed stress-responsive genes and antioxidant enzymes [216] Ascophyllum nodosum Arabidopsis Downregulated stress-responsive negative growth regulator [217] Ecklonia maxima Chicory plants Enhanced physiological traits (relative water content, water use efficiency, chlorophyll content, nutrient uptake) [218] Heat stress Ascophyllum nodosum Spinach Improved germination percentage and germination speed, and reduced hydrogen peroxide and malondialdehyde content [219] Seaweed extract Bentgrass Enhanced tolerance [220] 2.6.5. Higher Plant Extract…”
Section: Seaweed Extractmentioning
confidence: 99%